1980
DOI: 10.1159/000149110
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Conversion from HBeAg to HBeAg by Degradation of Hepatitis B Core Particles

Abstract: Highly purified and homogenous hepatitis B core particles were obtained from an autopsy liver. The core particles consisted mainly of an electrophoretically single major polypeptide with a molecular weight of 20,000 daltons. When antigenic conversion from hepatitis B core antigen (HBeAg) to hepatitis B e antigen was achieved by treating these core particles by sonication or by passing them through an anti-HBc IgG-conjugated Sepharose 4B column, no appreciable changes were found in the above protein composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1

Year Published

1980
1980
1988
1988

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
(13 reference statements)
6
27
1
Order By: Relevance
“…wt. 21000 to 21500 is the only dominant polypeptide detectable in core particles that share the antigenicities of both HBcAg and HBeAg (Ohori et al, 1980a;Mackay et al, 1981 ;Yamaki et al, 1982). Furthermore, we found that a polypeptide with a tool.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…wt. 21000 to 21500 is the only dominant polypeptide detectable in core particles that share the antigenicities of both HBcAg and HBeAg (Ohori et al, 1980a;Mackay et al, 1981 ;Yamaki et al, 1982). Furthermore, we found that a polypeptide with a tool.…”
Section: Introductionmentioning
confidence: 61%
“…In this phase, only HBeAg/1 is released from core particles and their morphology does not change at all. A second phase reaction is caused by acidic buffer (lower than pH 4.5), heat treatment at 100 °C for 10 s (Ohori et al, 1980a), sonication or 8 M-urea treatment. In another paper , we predicted the secondary structure of the polypeptide deduced from the nucleotide sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The close physical correlation between HBeAg and Dane particles was examined earlier (Ohori et al, , 1980Takahashi et al, 1979;Yoshizawa et al, 1979), and HBeAg is now Yamada et al, 1979Yamada et al, , 1981. In earlier reports from our laboratory (Yamada et al, 1979(Yamada et al, , 1981, it was demonstrated that free 'small' mol.…”
Section: Introductionmentioning
confidence: 65%